Christological orientation of Marian cult according to Saint John Paul II - Wojtczak, Adam (Studia Teologiczne Białystok Drohiczyn Łomża, 2021)
John Paul II’s pontificate is characterized by Marian teaching, which is abundant not only in the doctrine, but it is inspirational from the cultic point of view. The papal domain is the care for Christological orientation of Marian piety. On the one-hundredth anniversary of the Pope’s birth, the article reveals why Christocentrism belongs to the nature of Marian cult and how it is specifically manifested. These issues delineate its basic structure. At first, the formula “through Jesus to Mary” comes to the foreground, which is balanced by the traditional formula “through Mary to Jesus”. The next point focuses on the contemplation of the Christ’s face in Mary’s “school” (the Eucharist and the Rosary). In order to Christologically renew Marian piety, it is beneficial to utilize the model of Marian mediation in Christ (Maria in Christo Mediatrix), which is motherly and subjected to His mediation. Pope Wojtyła is also a witness and a teacher of entrusting himself to Mary in a filial manner, which originates in Christ and ultimately leads to Him. Finally, the papal cum, which expresses the fact that we come to Jesus not only “imitating” Mary, but also “with” Mary. In this respect the most prominent are the encyclicals Redemptoris Mater and Ecclesia de Eucharistia, apostolic letter Rosarium Virginis Mariae, as well as Marian catecheses given by the Pope between the years 1995 and 1997.